A demonstration of solid-state white light-emitting electrochemical cells using the integrated on-chip plasmonic notch filters. Issue 8 (26th January 2016) - Lee, Ya-Ju; Lin, Chia-Ching; Lee, Hsiao-Chin; Yao, Yung-Chi; Sarma, Monima; Su, Hai-Ching; Yang, Zu-Po; Wong, Ken-Tsung
Abstract : A realization of white light-emitting electrochemical cells by employing the integrated plasmonic notch filter to tailor the electroluminescence spectrum. Abstract : In this study, we demonstrate solid-state white light-emitting electrochemical cells (LECs) using an integrated plasmonic notch filter to tailor the electroluminescence (EL) spectrum of non-doped blue-green emissive material. The plasmonic notch filter is composed of randomly distributed silver nanoparticles (Ag-NPs) embedded in the anode contact of indium tin oxide (ITO). This plasmonic notch filter strongly absorbs green light due to local surface plasmon (LSP) resonance of the Ag-NPs embedded in ITO. Thus, the emission green light of the solid-state LEC is strongly suppressed, leaving the blue and red light output to generate a white EL emission. Moreover, the duration of white EL can be maintained for a longer time under operation, which overcomes the issues regarding the short lifetime of white EL generated by the microcavity effect. In addition, the Ag-NPs can be readily fabricated by the thermal annealing of Ag film, which is compatible with current fabrication technologies typically used in light-emitting diode (LED) industry. Therefore, solid-state white LECs using an integrated on-chip plasmonic notch filter have great potential for applications in solid-state lighting.